(3EOGQI GdCYeGd GdMchejIs - (3GdUjQaj(B, (3eMeOs ((3GdGScfOQjI(B;(3GdbGgQI(B,(3WjHI ddfTQ hGdJhRjYs (3MhQS GdOhdjI ddfTQ hGdJhRjYs, 2005)
(3eGgjI heaghe GdGOGQI GdYGeI, GdJNWjW aj GdGOGQI GdYGeI, GdSjGSI GdYGeI, GdHjQhbQGWjI, GdJfXje aj GdGOGQI GdYGeI, GdefXeGJ GdYGeI, GdGOGQI GdeMdjI, GOGQI GdCaQGO aj GdefXeGJ GdYGeI(B.s
Keywords: (3EOGQI GdCYeGds; (3EOGQI GdCaQGOs; (3GdEOGQI GdYGeIs; (3GdJNWjWs